PSYCHOLOGICAL MANIFESTATIONS OF STORY HRYHIR LUZHNICKIY «СHILD» - Vivcharyk, N. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article attemps to carry out the analysis of the short prose of Hryhir Luzhytskyi and its poetics. The semantics of colors, which play a major part in the texts, i ascertained. The attention is paid to the associative development of the plotline in novella «The Child», specifics of the narration and confliсt, which accumulate philosophical problems.